The Influence of Family Strength on the Quality of Pregnancy - Euis Sunarti; Hidayat Syarief; Hardinsyah .; Ratna Megawangi; Asep Saefuddin; Husaini . (Media Gizi dan Keluarga, 2003)
The Objectives of this study were to anaylize the influence of family strength on pregnancy quality. The data were analyzed from the study of